PENGARUH MENGUNYAH PERMEN KARET RENDAH GULA TERHADAP PENINGKATAN SEKRESI SALIVA PADA PASIEN YANG MENJALANI TERAPI HEMODIALISA - Silalahi, Rini Debora; Sembiring, Ripando Jhon Satria; Purba, Bahtera David (INSTITUT KESEHATAN DELI HUSADA, 2024)
Abstract Background: Chronic kidney failure is a health problem that needs special attention. The number of end-stage renal failure sufferers undergoing hemodialysis therapy increases every year. Hemodialysis therapy is an appropriate action to replace kidney function with a method of supplying fluid intake which results in most patients complaining of dry mouth (xerostomia). Objective: Fluid restriction generally causes dry mouth in hemodialysis (HD) patients. The observed effects of chewing gum on the amount of saliva, interdialytic weight gain (IDWG), and thirst levels in HD patients are inconsistent. We are considering whether gum can modulate this third parameter in patients undergoing HD. Method: This study used purposive sampling with 37 patients on HD. Thirst levels were measured using a self-rated visual analogue scale (VAS) and the summed xerostomia inventory (SXI). Results: The level of thirst after blood washing was significantly lower in the gum chewing group compared to the control group with a p value (0.000) <0.005. The amount of saliva was higher in the gum group than in the control group before dialysis, but the amount of saliva was comparable between the groups after dialysis. In addition, the amount of saliva was not associated with IDWG in patients undergoing HD before or after dialysis. Conclusion: Chewing gum can relieve thirst but does not affect the amount of saliva and IDWG in HD patients. Therefore, we suggest that chewing gum may be a useful approach to treat dry mouth and thirst in HD patients.